Lethal liquorice lollies (liquorice abuse causing pseudohyperaldosteronism) - Flores Robles, B J (BMJ Publishing Group, 2013)
A 47-year-old woman was admitted to the emergency department with a history of asthenia, periorbital and lower limbs oedema, associated with hypokalaemia and increased blood pressure levels. Metabolic and renal causes were initially investigated as thyroid disease, Cushing syndrome and tubulopathies were excluded during the first week of admission. However, further questioning of the patient, revealed that she had been consuming several sachets of raw liquorice lollies (ignored amount) obtained from a herbalist a month ago. Based on the history and clinical findings, liquorice poisoning was highly suspected; an apparent mineralocorticoid excess secondary to ingestion of liquorice. Afterwards, levels of aldosterone and plasma renin activity were measured and found low 3 weeks later; therefore, our clinical suspicion was established. During the patient's stay at the hospital, liquorice was stopped and potassium supplements were started. Subsequently, a week after, the patient fully recovered without any significant sequelae.